Chemical Characteristics and Allergenicity Alterations Induced by Heating in Mackerel Tuna (Euthynnus affinis) Powder Production - Z. Khaerani; N. Sri Palupi; N. Wulandari; F. Kusnandar (Journal of Food Quality and Hazards Control)
Background: Parvalbumin, the main allergen in mackerel tuna (Euthynnus affinis), is present in higher concentrations in white meat relative to red. Parvalbumin reduction can be achieved through heating methods such as pressure heating (autoclaving) and steaming. This study aimed to evaluate the impact of these methods on the nutritional value of mackerel tuna fish powder, analyze molecular weight profiles during processing, and assess allergenicity across different meat types. Methods: Fish powder production begins by separating the meat into three types: white, red, and mixed with a weight ratio of red meat to white meat of 1:3 (w/w). Fifteen samples—five per meat type, including fresh, post-heating, and post-flour processing were analyzed in January 2024, with each treatment performed in duplicate. Nutritional composition (proximate analysis), protein molecular weight (Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis), and allergenicity (Enzyme-Linked Immuno-Sorbent Assay kit) were evaluated. Statistical analysis was conducted using SPSS 25.0, with significance set at 5%. Data were analyzed using t-tests and Analysis of Variance (ANOVA). Duncan’s Multiple Range Test (DMRT) was applied to evaluate significant differences. Results: Pressure heating and steaming both significantly reduced moisture content and increased protein levels in fish powder. Pressure heating more effectively reduced allergenic protein bands, especially parvalbumin, compared to steaming. Moreover, pressure heating achieved greater allergenicity reduction in white (85.49%), red (84.24%), and mixed meats (83.01%). White meat exhibited the highest parvalbumin levels, followed by mixed and red meats. Conclusion: Both heating methods effectively reduced allergenicity. Based on allergenicity and economic factors, mixed meat types are recommended.